PENGARUH SISTEM REWARD DAN PUNISHMENT TERHADAP PENINGKATAN KUALITAS PELAYANAN DIKANTOR BPJS KESEHATAN PROVINSI GORONTALO - Rizal (LP2M Universitas Bina Mandiri Gorontalo, 2018)
This research aims at finding out the influence of reward and punishment system towards quality advancement in the office of the National Health and Social Care Security of Gorontalo Province. Data collection techniques used in this research are observation, interview and documentation. Whereas, the Analysis method of this research is quantitative by obtaining primary and secondary data as sources. This research applies deductive approach. The population of this study is entirely employees of the office of the National Health and Social Care Security of Gorontalo Province in which 42 people as respondents. The samples are taken by applying saturated sampling technique. Based on the result analysis, it is seen that t count from a variable of reward obtained t count 5,419 > ttable1,682 and by significant level 0,000 <0,05. Thus, the hypothesis of Ha1, in this case, is accepted, in which the Reward makes significant influence towards quality advancement in the office of the National Health and Social Care Security of Gorontalo Province. Meanwhile, giving punishment does not significantly influence towards quality advancement in the office of Health BPJS of Gorontalo Province. It is proved from t count 0,311 is lower than the value of table 1,682 and shows that the value of significance level is 0,757 for which the value is higher than 0,05. Therefore, the hypothesis of Ha2 is rejected, which means that the system of punishment does not significantly influence towards quality advancement in the office of the National Health and Social Care Security of Gorontalo Province. Based on the result of the ANOVA test, it is obtained the value of Fcount is 10,535 with significant level is 0,000. Value of Fcount compares to the value of Ftable is 3,23. Thus, it is obtained that Fcount> Ftable or by paying attention to significance level F=0,000 which means > 0,05 that means there is influence simultaneously between Reward and Punishment towards quality advancement in the office of the National Health and Social Care Security of Gorontalo Province. It is expected that the National Health and Social Care Security for always giving opportunity in learning and development for employees to advance their competency, and an effort of doing the jobs, employees need to improve the working quality and giving service for customers, keep their politeness, and be equipped by adequate facility and infrastructure